2004
DOI: 10.1053/j.gastro.2004.07.006
|View full text |Cite
|
Sign up to set email alerts
|

CFTR Cl− channel function in native human colon correlates with the genotype and phenotype in cystic fibrosis

Abstract: Specific CFTR mutations confer residual CFTR function to rectal epithelia, which is related closely to a mild disease phenotype. Quantification of rectal CFTR-mediated Cl- secretion may be a sensitive test to predict the prognosis of CF disease and identify CF patients who would benefit from therapeutic strategies that would increase residual CFTR activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 49 publications
11
125
1
2
Order By: Relevance
“…genet.sickkids.on.ca/cftr/app). Furthermore, the sweat chloride level, a parameter directly reflecting CFTR activity in vivo and thus a widely used diagnostic tool for CF, in patients taking Vx-770 (19,20) were still higher than those found in patients with mild-form CF (19,20,40), suggesting that Vx-770 alone is insufficient to completely rectify the dysfunction associated with the G551D mutation in vivo. Furthermore, recent clinical trials suggest that treatments with drugs that can improve the trafficking of ΔF508-CFTR may not be sufficient to ameliorate the clinical symptoms in patient carrying the ΔF508 mutation (1) presumably because this most common pathogenic mutation causes deficits in both membrane expression and gating (41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 95%
“…genet.sickkids.on.ca/cftr/app). Furthermore, the sweat chloride level, a parameter directly reflecting CFTR activity in vivo and thus a widely used diagnostic tool for CF, in patients taking Vx-770 (19,20) were still higher than those found in patients with mild-form CF (19,20,40), suggesting that Vx-770 alone is insufficient to completely rectify the dysfunction associated with the G551D mutation in vivo. Furthermore, recent clinical trials suggest that treatments with drugs that can improve the trafficking of ΔF508-CFTR may not be sufficient to ameliorate the clinical symptoms in patient carrying the ΔF508 mutation (1) presumably because this most common pathogenic mutation causes deficits in both membrane expression and gating (41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 95%
“…The degree of CFTR activity in the intestine can be measured using an electrophysiological test: the intestinal current measurement (ICM) [62]. Studies have shown that ICM correlates with CFTR genotype and phenotype [63], and diagnostic sensitivity in difficult CF diagnosis remarkably reaches 100% [64], making this tool also a potentially useful CF biomarker. Notably, defects in CFTR-mediated chloride transport correlated with CF disease severity, suggesting that ICM accurately reflects the level of CFTR functionality.…”
Section: Cftr Correctorsmentioning
confidence: 99%
“…No studies were found on reliability. ICM has been shown to discriminate between patients with cystic fibrosis and healthy individuals [37,[80][81][82][83][84][85][86]] and, at a group level, can discriminate between pancreatic sufficient and insufficient patients [35]. Similar to the sweat test and the NPD, patients with cystic fibrosis who were grouped according to their ICM result have been shown to differ in disease presentation: the more chloride secretion measured in the rectal mucosa, the milder the disease presentation [35,37,82].…”
Section: Clinimetrics Of Cftr Bio-assaysmentioning
confidence: 99%